Neuroprotective effects of oleuropein: Recent developments and contemporary research. Issue 12 (30th October 2021) - Butt, Masood Sadiq; Tariq, Urwa; Iahtisham‐Ul‐Haq,; Naz, Ambreen; Rizwan, Muhammad
Abstract: Neurological disorders are increasing at a faster pace due to oxidative stress, protein aggregation, excitotoxicity, and neuroinflammation. It is reported that the Mediterranean diet including olives as a major dietary component prevents and ameliorates neurological anomalies. Oleuropein is the major bioactive component in different parts of the Olive ( Olea europaea L.) tree. Several mechanisms have been reported for the neuroprotective role of oleuropein including induction of apoptosis and autophagy, enhancing the antioxidant pool of the cerebral region, decreasing the unnecessary release of proinflammatory cytokines and chemokines by deactivating the microglia cells and astrocytes thus preventing the occurrence of neuroinflammation. Regular intake of oleuropein seems to be correlated with decreased risks of neural disorders including Alzheimer's, Parkinson's, strokes, depression, anxiety, epilepsy, and others. This review majorly discusses the chemistry, biosynthesis, and metabolism of oleuropein along with an updated vision of its neuroprotective role in counteracting the acute and chronic neurodegenerative and neuropsychiatric disorders. Moreover, mechanisms by which oleuropein may prevent neurodegeneration are reviewed. Practical application: Neurological disorders are negatively affecting the health and life quality of individuals around the globe. Although various medicinal solutions are available to tackle such ailments, none has proven to fully cure and being deprived of side effects. In this respect, the prevention of such disorders using natural remedies may be an effective strategy to overcome the incidence of the increasing cases. Furthermore, the natural compounds provide a safer alternative to pharmaceutical drugs. Hence, oleuropein from olive tree products is found to be efficacious against neurological disorders. This review provides an updated insight on the positive effects of oleuropein against neurodegenerative and neuropsychiatric disorders. The diet practitioners and nutraceutical companies may benefit from the provided information to design and develop strategies to improve the mental health of suffering individuals. Abstract : Oleuropein exerts neuroprotective role by maintaining the integrity of blood brain barrier. Being a potent antioxidant, it inhibits protein aggregation, DNA damage and mitochondrial fission. As an antiinflammatory agent, it prevents neural inflammation, inhibits superfluous activation of microcytes & astrocytes and suppresses the release of proinflammatory cytokines. Besides, oleuropein also regulates levels of neurotransmitters in synaptic cleft, cellular calcium influx and behavioral responses to various endogenous/exogenous stimuli.